Engineering Hydrogen Sulfide Production and Cadmium Removal by Expression of the Thiosulfate Reductase Gene (phsABC) from Salmonella enterica Serovar Typhimurium in Escherichia coli - Bang, Sang-Weon (American Society for Microbiology, 2000)
The thiosulfate reductase gene (phsABC) from Salmonella enterica serovar Typhimurium was expressed in Escherichia coli to overproduce hydrogen sulfide from thiosulfate for heavy metal removal (or precipitation). A 5.1-kb DNA fragment containing phsABC was inserted into the pMB1-based, high-copy, isopropyl-β-d-thiogalactopyranoside-inducible expression vector pTrc99A and the RK2-based, medium-copy, m-toluate-inducible expression vector pJB866, resulting in plasmids pSB74 and pSB77. A 3.7-kb DNA fragment, excluding putative promoter and regulatory regions, was inserted into the same vectors, making plasmids pSB103 and pSB107. E. coli DH5α strains harboring the phsABC constructs showed higher thiosulfate reductase activity and produced significantly more sulfide than the control strains under both aerobic and anaerobic conditions. Among the four phsABC constructs, E. coli DH5α (pSB74) produced thiosulfate reductase at the highest level and removed the most cadmium from solution under anaerobic conditions: 98% of all concentrations up to 150 μM and 91% of 200 μM. In contrast, a negative control did not produce any measurable sulfide and removed very little cadmium from solution. Energy-dispersive X-ray spectroscopy revealed that the metal removed from solution precipitated as a complex of cadmium and sulfur, most likely cadmium sulfide.